Didacticism in Exodus?: elements of didactic genre in Exodus 1-15 - Berge, Kåre (Scandinavian journal of the Old Testament, 2008)
This article argues that there is a "torah didacticism" in the Exodus narrative, especially in the presentation of the plagues. This is most visible in Exod 15,22-26, which belongs to the final Pt redaction and, accordingly, appears as one of the first inner-biblical interpretations of the story. A similar tora-didactical reading, influenced by wisdom, also appears in the probably late narrative rehearsals of the exodus in the Psalms. A study of Exod 1-15 reveals genre elements of sapiential didactic tales, which indicate a didactic pragmatic momentum, force, or impetus in the story. This conclusion is confirmed through a comparison between the Exodus story (as presented in the non-P parts) and the so-called prophetic didactic or ethical legenda as described by A. Rofé. This didactic function is most visible in textual elements that literary critics have identified as late redactional insertions. From this (late redactional) perspective of torah didacticism, the article also reads the story for its narrational coherence. As a conclusion, our study indicates that torah didacticism is a perspective that late, inner-biblical redaction and interpretation of the Exodus narrative has put on the story. At this point, our conclusion comes close to E. Otto's statements about the function of Moses in late Pt redaction.